2020
DOI: 10.5116/ijme.5ea6.ae73
|View full text |Cite
|
Sign up to set email alerts
|

The effect of simulator fidelity on procedure skill training: a literature review

Abstract: Objective: To evaluate the effect of simulator fidelity on procedure skill training through a review of existing studies. Methods: MEDLINE, OVID and EMBASE databases were searched between January 1990 and January 2019. Search terms included "simulator fidelity and comparison" and "low fidelity" and "high fidelity" and "comparison" and "simulator". Author classification of low-and high-fidelity was used for non-laparoscopic procedures. Laparoscopic simulators are classified using a proposed schema. All included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 44 publications
1
42
0
4
Order By: Relevance
“…However, PBT can be more time-consuming and require more repetitions compared to traditional interval training. Accordingly, simple and readily available systems for SBST have been developed, and studies have demonstrated that laparoscopic psychomotor skills can be effectively trained and acquired using basic, inexpensive, and low-fidelity box training models (BTs) [11][12][13]. Portable BTs allow trainees to engage in training at home at their own discretion outside simulation facilities' opening hours [14,15].…”
mentioning
confidence: 99%
“…However, PBT can be more time-consuming and require more repetitions compared to traditional interval training. Accordingly, simple and readily available systems for SBST have been developed, and studies have demonstrated that laparoscopic psychomotor skills can be effectively trained and acquired using basic, inexpensive, and low-fidelity box training models (BTs) [11][12][13]. Portable BTs allow trainees to engage in training at home at their own discretion outside simulation facilities' opening hours [14,15].…”
mentioning
confidence: 99%
“…Although the educational value of simulator-based training was found to be valuable, the influence of realism is discussed controversially, with studies reporting better, worse, or similar outcomes after training on a low-fidelity simulator as compared with a highfidelity simulator. [20][21][22][23][24][25] In addition to face validity, construct validity is regarded as one of the most important aspects of simulator evaluation. Construct validity determines whether the device simulates the given task as in real life and thus can differentiate between a novice and an expert.…”
Section: Discussionmentioning
confidence: 99%
“…The questionnaires on face validity were answered by 39 medical students: 19 men (49%) and 20 women (51%). Their average age was 25.3 years (range, [21][22][23][24][25][26][27][28][29][30][31]. Nine students had completed vocational training in a medical profession (nurse) prior to their medical studies.…”
Section: Demographic Characteristicsmentioning
confidence: 99%
“…Por lo que el aprendizaje a través de simulación e interacción con elementos clínicos en ambientes simulados, se ha convertido en una herramienta pedagógica de alta efectividad en el campo clínico, para la preparación de profesionales competentes, capaces de mejorar los procesos de atención e intervención (Weller, 2012). La literatura describe diferentes modelos educativos que se utilizan en simulación clínica y por ejemplo: 1) simuladores en forma de fantoma, que proporcionan elementos de retroalimentación; 2) simuladores virtuales y programas de computación, que son utilizados para aumentar las habilidades prácticas de los estudiantes en procesos de intervención invasiva en pacientes y 3) entornos controlados con aparatos para la medición de habilidades clínicas, herramienta ampliamente utilizada en la educación basada en casos clínicos (Kawarai et al, 2020).…”
Section: Introductionunclassified
“…La de mediana fidelidad combina el uso de una parte anatómica con programas computacionales, que permiten al instructor manejar variables fisiológicas con el fin de desarrollar una competencia, por ejemplo, la reanimación cardiopulmonar. Y la de alta fidelidad integra múltiples variables fisiológicas para crear escenarios realistas con fantomas de tamaño real con el fin de desarrollar competencias técnicas, no técnicas y el manejo de crisis (Kawarai et al, 2020).…”
Section: Introductionunclassified